2017
DOI: 10.1002/hpm.2470
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators for implementation of family medicine–oriented model of primary care in Bosnia and Herzegovina: A qualitative study

Abstract: Although many steps forward have been made in the reform and implementation of the family medicine-oriented model of primary health care in Bosnia and Herzegovina, our results revealed that there is still much room for improvement. Particular attention should be paid to establishing common goals and reaching mutual understanding with key stakeholders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…COREQ guideline (Consolidated Criteria for Conducting and Reporting Qualitative Research), 32‐item checklist, was used for structuring and reporting the study . Interview Guide (Table ) was created by investigators based on previous research and was finalized after pilot FG with a group of six nurses, representing the baccalaureate nurses to be involved in the main study. Questions were open‐ended, semi‐structured, reflective, answerable, and nondirective.…”
Section: Methodsmentioning
confidence: 99%
“…COREQ guideline (Consolidated Criteria for Conducting and Reporting Qualitative Research), 32‐item checklist, was used for structuring and reporting the study . Interview Guide (Table ) was created by investigators based on previous research and was finalized after pilot FG with a group of six nurses, representing the baccalaureate nurses to be involved in the main study. Questions were open‐ended, semi‐structured, reflective, answerable, and nondirective.…”
Section: Methodsmentioning
confidence: 99%
“…Similar findings were also reported by other authors; Arasu et al [9] reported on general practitioners' acknowledgment of the importance of weight and lifestyle management in PCOS, but their practices were influenced by various barriers (time constraints, lack of financial reimbursement, weight management being professionally unrewarding, perceived lack of patient motivation, costs of accessing allied health professionals and their unavailability in certain locations). While we did not examine such factors in our study, at least some of the above-mentioned barriers could easily be recognized as present in our health care system as well and were indeed reported in the recent study investigating factors influencing the implementation of family medicine in Bosnia and Herzegovina [39] . Three participants reported advising vitamin D supplements.…”
Section: Discussionmentioning
confidence: 85%
“…The scores in these domains may have been better in other countries in comparison to Bosnia and Herzegovina due to differences in primary health care system organization. First, primary care reform in Bosnia and Herzegovina is still not complete, and healthcare delivery calls for improvement ( 29 ). Following the trend in Western European countries, governmental institutions could transfer tasks from the medical to the nursing profession by employing a higher number of nurses with a bachelor’s degree, well-trained to provide chronic patient care.…”
Section: Discussionmentioning
confidence: 99%